Comprehensive Modeling of Spinal Muscular Atrophy in Drosophila melanogaster - Spring, Ashlyn M.; Raimer, Amanda C.; Hamilton, Christine D.; Schillinger, Michela J.; Matera, A. Gregory (Frontiers in Molecular Neuroscience, 2019)
Spinal muscular atrophy (SMA) is a neurodegenerative disorder that affects motor neurons, primarily in young children. SMA is caused by mutations in the Survival Motor Neuron 1 (SMN1) gene. SMN functions in the assembly of spliceosomal RNPs and is well conserved in many model systems including mouse, zebrafish, fruit fly, nematode, and fission yeast. Work in Drosophila has primarily focused on loss of SMN function during larval stages, primarily using null alleles or strong hypomorphs. A systematic analysis of SMA-related phenotypes in the context of moderate alleles that more closely mimic the genetics of SMA has not been performed in the fly, leading to debate over the validity and translational value of this model. We therefore examined fourteen Drosophila lines expressing SMA patient-derived missense mutations in Smn, with a focus on neuromuscular phenotypes in the adult stage. Animals were evaluated on the basis of organismal viability and longevity, locomotor function, neuromuscular junction structure, and muscle health. In all cases, we observed phenotypes similar to those of SMA patients, including progressive loss of adult motor function. The severity of these defects is variable, and forms a broad spectrum across the fourteen lines examined, recapitulating the full range of phenotypic severity observed in human SMA. This includes late-onset models of SMA, which have been difficult to produce in other model systems. The results provide direct evidence that SMA-related locomotor decline can be reproduced in the fly and support the use of patient-derived SMN missense mutations as a comprehensive system for modeling SMA.